Plastic Purge: How to use less plastic, eat better, keep toxins out of your body, and help save the sea turtles! - SanClements, Michael (St. Martin's Griffin, 2014)
SanClements has put together the most up-to-date and scientifically-backed information available to explain how plastics release toxins into your body and the effect they have on your and your children's health. Both approachable and engaging, Plastic Purge provides easy-to-follow advice for how to use less plastic, thereby reaping the benefits such as eating a healthier diet and living with less clutter.